Pressure-induced electronic and structural phase transitions in Dirac semimetal Cd3As2: Raman study - Gupta, Satyendra Nath; Muthu, D. V. S.; Shekhar, Chandra; Sankar, R.; Felser, Claudia; Sood, A. K. (EPL - Europhysics Letters, 2017)
We report on the high-pressure Raman study of Cd3As2, a three-dimensional Dirac semimetal, up to 19GPa at room temperature. Our study shows that light scattering by intervalley and intravalley density fluctuations give rise to electronic Raman scattering (ERS), with Lorentzian-like lineshape at low frequency. The strength and linewidth of the ERS are pressure dependent and exhibit a significant drop at Pc1 = 2.5GPa, signifying a breakdown of the Dirac semimetal to a semiconducting phase. The first phase transition at Pc1 is also clearly identified by the significant changes in the pressure derivatives of phonon frequencies and linewidths. Pressure dependence of phonon parameters also reveal a second phase transition at Pc2 = 9.5GPa, being reported for the first time. This semiconductor-to-semiconductor transition coincides with the abrupt changes seen in the activation energy (band gap) of the semiconductor phase.
CRIS-Team Scopus Importer:2022-04-14